Routledge Handbook of Public Policy in Africa - Onyango, Gedion (Routledge International Handbooks, 2022)
This Handbook provides an authoritative and foundational disciplinary overview of African Public Policy and a comprehensive examination of the practicalities of policy analysis, policymaking processes, implementation, and administration in Africa today. The book assembles a multidisciplinary team of distinguished and upcoming Africanist scholars, practitioners, researchers and policy experts working inside and outside Africa to analyse the historical and emerging policy issues in 21st-century Africa. While mostly attentive to comparative public policy in Africa, this book attempts to address some of the following pertinent questions: • How can public policy be understood and taught in Africa? • How does policymaking occur in unstable political contexts, or in states under pressure? • Has the democratisation of governing systems improved policy processes in Africa? • How have recent transformations, such as technological proliferation in Africa, impacted public policy processes? • What are the underlying challenges and potential policy paths for Africa going forward? The contributions examine an interplay of prevailing institutional, political, structural challenges and opportunities for policy effectiveness to discern striking commonalities and trajectories across different African states. This is a valuable resource for practitioners, politicians, researchers, university students, and academics interested in studying and understanding how African countries are governed.